Educational Case Report: When you look for one thing and find another - G. Makrynos; C. Ntounias; G. Farantos; G. Dounias (European Scientific Journal, ESJ, 2024)
Aims and scope: The purpose of this article is to present a case study to conclude education in Occupational Health. We intend to examine the possibility of TBc transmission in the workplace following an incident. Methods:  After verifying the information, all employees in contact with hospitalized patient were checked with tuberculin test and chest X-ray to ensure about possible transmission of Tbc. We surveyed the scientific literature on TB screening programmes in workplaces and the occupational characteristics of workers exposed to asbestos, particularly marine carpenters, for potential respiratory health risks due to daily exposure to fine particles and wood dust. Thus, the literature specifically on mesothelioma and other health problems in marine carpenters was investigated.Findings: 27/95 employees were found Mantoux positive but no TBc transmission was verified. Instead, a carpenter was found with pulmonary fibrosis.  Special tests (BAL) found asbestos fibers. An accurate study of the worker's occupational history showed previous exposure while working in the shipyard.Discussion: The laboratory plays an essential role, since the surveillance of bacteriologically confirmed cases allows the most reliable comparisons, and because of the importance of the identification of drug resistance. The incidental finding of a case of mesothelioma in a carpenter was investigated in detail. Unfortunately, mesothelioma patients have a very aggressive cancer and often do not survive long enough for their personal injury lawsuits to become final.Conclusion:  For Public Health practice control for transmission of a known infection [TBc] maybe lead us to other findings. Then occupational exposure history can establish the correct diagnosis. In investigating the causes of workers' diseases, Ramazzini’s teaching remain relevant.